2018
DOI: 10.1007/s00394-018-1787-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimated dietary intake of polyphenols in European adolescents: the HELENA study

Abstract: The current study provided for the first time numbers on the total polyphenol intake and their main food sources in a heterogeneous group of European adolescents. Major differences with adult populations are the lower polyphenol consumption and the major food sources, such as chocolate and biscuits. The discussed determinants and polyphenol types already point to some important population groups that need to be targeted in future public health initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
41
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 48 publications
12
41
1
2
Order By: Relevance
“…In terms of food sources, coffee and tea (especially in the UK) were the main contributors of HCAs (caffeoyl‐ and feruloyl‐quinic acids). In the adolescent study, the mean daily total polyphenol intake (329 mg) was much lower compared to the studies in adult populations (Table ). Flavonoids were much better represented (75–76% of total polyphenols) than phenolic acids (17–19%).…”
Section: Dietary Intake Of Hydroxycinnamic Acids and Associated Healtmentioning
confidence: 65%
See 4 more Smart Citations
“…In terms of food sources, coffee and tea (especially in the UK) were the main contributors of HCAs (caffeoyl‐ and feruloyl‐quinic acids). In the adolescent study, the mean daily total polyphenol intake (329 mg) was much lower compared to the studies in adult populations (Table ). Flavonoids were much better represented (75–76% of total polyphenols) than phenolic acids (17–19%).…”
Section: Dietary Intake Of Hydroxycinnamic Acids and Associated Healtmentioning
confidence: 65%
“…As expected, a large heterogeneity in terms of mean intake and ranking of polyphenol classes has been seen among the different investigated cohorts. Two recent multi‐country European studies in adults (EPIC) and adolescents (HELENA) confirmed the variability of polyphenol intake at European level. In the adult study, the mean total polyphenol daily intake was the highest in Denmark (1786 mg for men and 1626 mg for women) and the lowest in Greece (744 mg in men and 584 mg in women).…”
Section: Dietary Intake Of Hydroxycinnamic Acids and Associated Healtmentioning
confidence: 73%
See 3 more Smart Citations